Spinous Process Combined With a Titanium Mesh Cage as a Bone Graft in the Stability Reconstruction of Lumbar or Lumbosacral Spinal Tuberculosis - Zhang, Hongqi; Xiao, Lige; Tang, Mingxing; Yang, Guanteng (Frontiers in Surgery, 2022)
Background Autogenous bone grafts, such as iliac bone or rib struts, have been used in the anterior reconstruction of spinal tuberculosis (STB) and have their own benefits and limitations. Here, we introduced a new method, the spinous process (SP), combined with a titanium mesh cage (TMC) as a bone graft in the stability reconstruction of lumbar or lumbosacral STBs. By retrospectively comparing patients who received SP+TMC to traditional TMC bone grafts or allogeneic bone grafts in terms of safety, efficacy and cost-effectiveness, we aimed to evaluate whether SP+TMC could be a possible alternative method. Methods From 2010 to 2018, 69 patients who underwent one-stage posterior debridement with grafts and internal fixation within a single lumbar or lumbosacral segment were included in this study. Twelve patients who received SP combined with a TMC (SP+TMC, group A), 30 patients who received a TMC only (group B), and 27 patients who received allografts (group C) were included. Measurements including operative time, blood loss, length of hospital stay, visual analog scale (VAS) score, Oswestry Disability Index (ODI), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), American Spinal Injury Association Impairment (ASIA) grade, final follow-up (FFU) duration and postoperative complications were recorded. Radiological measurements, including the number of segments fixated, the number of pedicle screws used, the Cobb angle, pelvic parameters, and the bony fusion time, were reviewed. All outcomes were analyzed using SPSS 25. Results We found that the SP+TMC group had fewer fixation segments, fewer pedicle screws implanted, a shorter operative time, reduced blood loss, and a considerably lower hospital cost than allografts. In addition, the TMC group had a comparable clinical outcome with the TMC group regarding lower economic cost. Conclusion Our study demonstrates that compared to a TMC or allograft, the use of SP combined with a TMC as a bone graft is an effective and reliable approach for the surgical management of one-level lumbar or lumbosacral spinal tuberculosis, leading to effective restoration of spinal stability. Furthermore, this approach is a cost-effective structural bone grafting method, especially for patients in developing countries.